DATA ABOUT INVESTIGATION OF UREDINALES IN THE REPUBLIC OF NAGORNY KARABAKH (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
In the article data about distribution of Uredinales in the Republic of Nagorny Karabakh are presented. As a result of investigations 63 species from 9 genera of Uredinales are found. They are parasites on 61 species of wild plants and 12 species of cultivated plants. The widely-distributed species belonged to genera Puccinia (36 species) and Uromyces (11 species).
Keywords: distribution of $Uredinales$; species; genera